Universal scaling of weak localization in graphene due to bias-induced dispersion decoherence - R. Somphonsane; H. Ramamoorthy; G. He; J. Nathawat; S. Yin; C.-P. Kwan; N. Arabchigavkani; B. Barut; M. Zhao; Z. Jin; J. Fransson; J. P. Bird (My University, 2020)
The differential conductance of graphene is shown to exhibit a zero-bias anomaly at low temperatures, arising from a suppression of the quantum corrections due to weak localization and electron interactions. A simple rescaling of these data, free of any adjustable parameters, shows that this anomaly exhibits a universal, temperature- (T) independent form. According to this, the differential conductance is approximately constant at small voltages (V < k
Keywords: Anomaly (physics); Biasing; Weak localization; Graphene research and applications